Selection for Parameter  by Using Newton-Raphson Method - Wan Muhamad Amir Bin W Ahmad; Nyi Nyi Naing; Mohd Tengku Ariff Raja Hussein (STATISTIKA: Forum Teori dan Aplikasi Statistika, 2007)
Many problems in mathematics or statistics involve, at some point or another, solving an equation foran unknown quantity. To solve the problem many of methods are applied as such MaximumLikelihood Method, Least Square Method and Newton-Raphson Method and much more. One of thefamous methods is Newton Method. The Newton-Raphson method or Newton–Fourier method is anefficient algorithm for finding approximations to the zeros (or roots) of a real-valued function. As such,it is an example of a root-finding algorithm. It can also be used to find a minimum or maximum valueof such a function, by finding a zero in the function's first derivative. In this paper, we will work withNewton-Raphson method to estimate the value of for the use of transformation. The value of ,determine the kind of transformation should be done according to the data. These papers emphasizethe Newton Method in finding the value of by using C++ software.